PENGARUH KEPEMILIKAN INSTITUSIONAL, PROPORSI DEWAN KOMISARIS INDEPENDENT, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP MANAJEMEN LABA - Sulaiman Sarmo; Muttaqillah Muttaqillah; Muhdin Muhdin; Iwan Kusuma Negara (Jurnal Ilmiah Akuntansi Indonesia, 2020)
This study aims to see the effect of ownership effect, independent commissioner board proportion, firm size on earnings management. This research was conducted at manufacturing companies listed on the IDX 2015-2017, using several tests, namely classical assumptions and multiple regression. The results showed that institutional ownership, independent board representatives and firm size had no effect on earnings management. Meanwhile, leverage affects earnings management. The implication of this research is that if a company has leverage, then there is an indication to carry out earnings management with the aim that the company has profit so that there is the ability to pay the company's debt.